CLINICAL SUPERVISION TO IMPROVE TEACHER COMPETENCE IN LEARNING ACTIVITIES AT SMA NEGERI 1 TAPAKTUAN - Afnidar; Siti Mayang Sari; Akmaluddin; Fitriani Manurung (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study aim to increase teacher competence in carry out activity learning at SMAN 1 Tapaktuan . This study is school action research. Subject the study were teachers of SMAN 1 Tapaktuan who underwent clinical supervision as many as 8 teachers. Instrument study use questionnaire, observation, and documentation. Data analysis techniques using analysis descriptive qualitative and analysis quantitative. Research results show that clinical supervision capable to increase teacher competence in carry out activity in doing learning process, create lesson plan learning, competency of managing class , as well implementation evaluation and assessment results learning . Based on results study obtained as much as 87.5% get grade Good (B) or as many as 7 teachers